Volatilome evolution during storage and in vitro starch digestibility of high-power ultrasonication pretreated wholegrain Oryza sativa L. (December 2022) - Yang, Caijiao; Zheng, Yuanrong; Green, Brian D.; Zhou, Changyu; Pan, Daodong; Cao, Jinxuan; Wang, Libin; Cai, Zhendong; Xia, Qiang
Graphical abstract: Highlights: Volatilome evolution of sonicated wholegrain brown rice (WBR) was assessed. WBR starch digestibility affected by high-power ultrasound (HPU) was characterized. HPU-associated markers of WBR included aldehydes, acids, esters and 2-pentyl-furan. HPU pretreatments significantly inhibited the lipid oxidation during WBR storage. Untargeted and targeted methods supported the use of HPU processing of WBR grains. Abstract: The potential of high-power ultrasonication (HPU) to enhance the physicochemical stability of bran-containing cereal products has been demonstrated, but the information concerning how the wholegrain volatilome and key quality-related chemical reactions evolve responding to HPU remains scarcely reported. The objective of this work was to examine the headspace volatile fingerprinting features of sonicated wholegrain brown rice (WBR; 400 W, 28 kHz, 30 min) following an accelerated storage testing (37 °C, 20 days), and simultaneously to identify the key chemical reactions induced by ultrasonication. A total of 70 aroma compounds were identified by the untargeted headspace GC–MS, including 9 alkanes, 6 alkenes, 15 aldehydes, 6 furans, 12 ketones, 9 alcohols and 13 miscellaneous compounds. Multivariate statistical analysis demonstrated that HPU pretreatments before a storage process significantly influenced the volatilome evolution, as revealed by a clear classification between sonicated and unsonicated grains. Supervised orthogonal partial least squares discriminant analysis identified the volatiles including acetic acid, pentanoic acid, hexanal, ethyl hexanoate and 2-pentyl-furan as HPU-related markers, inferring that HPU mainly modified the chemical reactions involving lipid decomposition, free fatty acids oxidation and esterification. This was further confirmed by targeted monitoring of lipid peroxidation products, with 13.22–14.84 % of MDA contents reduced ( p  < 0.05) in sonicated samples after storage. Besides, the ultrasonic effects resulted in a slight improvement of in vitro starch digestibility of WBR samples depending on the rice ecotype. This investigation demonstrated the potential of HPU pretreatments for prolonging the oxidative stability of WBR grains, without significantly compromising digestion properties.